2011
DOI: 10.1186/1471-2458-11-846
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected decline in tuberculosis cases coincident with economic recession - United States, 2009

Abstract: BackgroundSince 1953, through the cooperation of state and local health departments, the U.S. Centers for Disease Control and Prevention (CDC) has collected information on incident cases of tuberculosis (TB) disease in the United States. In 2009, TB case rates declined -11.4%, compared to an average annual -3.8% decline since 2000. The unexpectedly large decline raised concerns that TB cases may have gone unreported. To address the unexpected decline, we examined trends from multiple sources on TB treatment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…157 Studies of unemployment trends and deaths due to causes related to infections, particularly pneumonia and tuberculosis, find that greater unemployment is associated with decreases in deaths due to infectious disease. 12,17,37,39,158 A potential pathway put forth in a recent study suggests that less economic activity reduces the spread of communicable disease such as pneumonia or flu for workers through the essential quarantine of being unemployed and staying home. 159 However, the mechanistic pathway for why we see this relation in mortality for older populations is still unclear.…”
Section: Infectious Diseasementioning
confidence: 99%
“…157 Studies of unemployment trends and deaths due to causes related to infections, particularly pneumonia and tuberculosis, find that greater unemployment is associated with decreases in deaths due to infectious disease. 12,17,37,39,158 A potential pathway put forth in a recent study suggests that less economic activity reduces the spread of communicable disease such as pneumonia or flu for workers through the essential quarantine of being unemployed and staying home. 159 However, the mechanistic pathway for why we see this relation in mortality for older populations is still unclear.…”
Section: Infectious Diseasementioning
confidence: 99%
“…Whether the costs of drugs are perceived as affordable will depend for a large part on who is bearing the burden: the patient or the healthcare system. For the patient, out-of-pocket expenses and indirect costs are a strong driver of healthcare-seeking behaviour and adherence to treatment [2][3][4]; whereas, for the healthcare system, drug and service delivery costs are important considerations. The recent economic recession has shown that financial constraints on healthcare systems can have detrimental effects on the incidence of infectious disease [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although the relationship between Human Immunodeficiency Virus (HIV) infection and TB is well described [32], we were not able to incorporate information on HIV status due to underreporting and lack of published HIV incidence and prevalence estimates in the United States by country of origin. We assumed current trends in TB cases will continue with cases declining in a linear pattern; however, trends can be affected by changes in behavior, policies, or other factors that influence population and immigration [20], [22]. Although the linear regression model was not a good fit for all countries, we showed that our prediction results were generally conservative in relation to more complex regression models.…”
Section: Discussionmentioning
confidence: 98%
“…Immigration, which is directly affected by national policies and socioeconomic factors [20], is an important consideration in the number of TB cases among foreign-born persons [21], [22]. Major changes in immigration patterns could alter our case count predictions.…”
Section: Discussionmentioning
confidence: 99%